Fabrication of hybrid organic solar cell using MEH-PPV : I-MWCNT as an active layer / Puteri Sarah Mohamad Saad - Mohamad Saad, Puteri Sarah (Institute of Graduate Studies, UiTM, 2014)
Attention in incorporating inorganic nanostructures into organic optoelectronic devices has been growing in the past few years. These so-called hybrid organicinorganic nanocomposites systems are being studied more closely due to its possibility in combining the advantageous characteristics of inorganic and organic components. Within a single composite, the properties can easily be changed or tuned by varying the size of nanoparticle, material composition, and concentration in the composites to match the device requirement. The most important thing, they can maintain the fabrication advantages of organic device such as easy processing, low production and material cost, and manufacturing the devices on large and flexible substrates. These are important in device application and commercialization. Therefore, research on improving the performance of organic solar cells by incorporating inorganic nanostructures in the organic materials has become important topic of research. The nanocomposited photoactive layer thin film which is MEH-PPV:MWCNT were prepared and characterized.